Ageing, Longevity and Savings: The Case of Morocco - Ghizlan Loumrhari (International Journal of Economics and Financial Issues, 2014)
In this paper we investigate empirically the relationship between population agings begins in Morocco and private savings. To do this, we use an overlapping generations model (OLG) using annual data from 1980 to 2010. Econometric estimates show that if the increase in the dependency ratio negatively affects the growth rate of savings, as predicted by the lifecycle theory, longevity to the contrary tends to stimulate the same savings. However, it seems that the first effect outweighs the second. Economic policies to promote private savings and incentives for households to have more children are needed to meet the challenge of severe aging population which will face Morocco in the coming decades.